Table of Content - -, (Journal of Islamic Sciences, 2023)
Table of Content:1. Study, Investigation and Interpretation (The first four verses of Surat Al-Baqarah) Written by: Al-Fadil Al-Yamani in his Book (Pearl Shells in Al-Kashaf Intricacies' Solution)Mr. Akram Mohammed Abdullah2. The book of Al-Hisbah, the Abodes and What pertains to Imam as well as Other Issues Written by the Scholar and Judge: Abdullah bin Mohammed bin Abdullah bin Hamza bin Abi Najm (died in 647 A.H.) – A study and an investigation –Dr. Mohammed Yahya Ahmed Abdullah Al-Qadi3. The verse of preserving money and not transgressing in Surat Al-Nisa: An analytical studyMr. Ahmed Mohamed Ahmed Al-Khawaldeh , Prof. Jihad Muhammad Faisal Al-Nuseirat4. The Purposes of Islamic Sharia Which Related to the Mandatory ProvisionMr. Abdullah Ahmed Ahmed Dahman5. Study and Investigation: Interpretation Surat Ibrahim for Al-Fadhel Al-Yemeni in His Note Durar Al-Sadaf Fi Hal Oqad Al-KashafDr. Omar Fuaini Omar Maqbol6. The impact of the difference in the significance of the absolute command on obligation in the jurisprudential branches.(Analytical، descriptive study)Dr. Rahma Abdullah Musleh Al-Warraq7. The method of scholar " Yaḥya Ibn-Aḥmad Ibn-Muẓaffar" in weighting and reasoning in his book "Al-Kawakib Al-Naiyira Al-kashifa li-Maanai Al-taḏkira" "Book of Al- Eibadat Enmudhajan"Dr. Fawakha Saleh Al-Gabri8. The judge bin Shamlah Bahanan and his book Neil Al-Maqsoud in explanation of Sunan abi Daoud from the chapter of what came in answering the invitation to the chapter of the desirability of feast: (transcription and commenting)Dr. Sawsan Ali Bazarah
Keywords: Journal of Islamic Sciences